Pattern of Drug Use For Dyspepsia In Outpatient Patients at dr. Zubir Mahmud Hospital - Sri Wastuti; Alfi Sulthan; Hepni Hepni (International Journal of Health Engineering and Technology, 2025)
Dyspepsia is one of the most common digestive problems found in the community. Symptoms felt such as heartburn, nausea, vomiting, decreased appetite, belching and feeling full quickly. This study aims to determine the pattern of drug use in outpatient dyspepsia patients at the dr. Zubir Mahmud Regional General Hospital. This study used a retrospective descriptive method conducted in January-December, data obtained from prescriptions for inpatient dyspepsia patients at the dr. Zubir Mahmud Regional General Hospital. The results showed that there were 2030 patients diagnosed with dyspepsia. The majority of dyspepsia disease occurred in women 54 people (55.67%) and at the age of 46-65 years consisting of 38 people (39.17%). The most commonly used type of drug is omeprazole 48 (26.22%), the most common drug preparation is capsule preparation 85 R/ (46.44%) and the most common drug class is the Proton Pump Inhibitor class as much as 85 R/ (46.44%).